Pengembangan Media Pop-Up Book Pada Pembelajaran Pancasila Untuk Meningkatkan Hasil Belajar Peserta Didik - Rosalina, Firda; Asmarani, Ratih; Faizi, Ahmad (IJPSE Indonesian Journal of Primary Science Education, 2024)
In improving learning activities is the need for a new learning environment through learning media. At the elementary school level, learning media is very important as a tool that can attract the attention of students so that the learning process becomes fun. In the era of technological advances, there is a lot of common sense in life, especially at the age of elementary school children. Thus it is necessary to strengthen material for students about divine values, human values, unity values, social values and justice values contained in Pancasila. The purpose of this study was to develop Pop-Up Book learning media through Pancasila learning to improve learning outcomes for fourth grade elementary school students. The type of development research used is the ADDIE model through five stages, namely analysis, design, development, implementation, and evaluation. Pop-Up Book media has met the quality criteria by obtaining an average score of 93.33% from validator experts, teachers and students with a very valid category and very decent media without improvement. While the implementation of the media, got 92,2% results from the results of the teacher and student questionnaire responses. The pre-test results before using the media obtained by students were 55% and the post-test results after using the media obtained an average value of 82%. The comparison before and after using the Pop-Up Book media was 27% so that the results of increasing student learning were obtained.